The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jbc.2021.100573
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of TRPV1 channels by phosphatidylinositol via functionally distinct binding sites

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…The striking overlap between PI and RTX in this site suggests the possibility that PI is an antagonist of vanilloids in TRPV1. Indeed, a recent study showed that PI inhibits TRPV1 in excised inside-out patches, and that inhibition is the strongest at low capsaicin concentrations and lost at high capsaicin concentration, suggesting that PI competitively inhibits capsaicin activation of TRPV1 (Yazici et al, 2021). A similar example of overlapping lipid-drug binding modes was also observed in TRPA1 structures in complex with the agonist, GNE551 (Suo et al, 2020;Liu et al, 2021; Figure 7B).…”
Section: Vanilloid Binding Sitesupporting
confidence: 55%
See 2 more Smart Citations
“…The striking overlap between PI and RTX in this site suggests the possibility that PI is an antagonist of vanilloids in TRPV1. Indeed, a recent study showed that PI inhibits TRPV1 in excised inside-out patches, and that inhibition is the strongest at low capsaicin concentrations and lost at high capsaicin concentration, suggesting that PI competitively inhibits capsaicin activation of TRPV1 (Yazici et al, 2021). A similar example of overlapping lipid-drug binding modes was also observed in TRPA1 structures in complex with the agonist, GNE551 (Suo et al, 2020;Liu et al, 2021; Figure 7B).…”
Section: Vanilloid Binding Sitesupporting
confidence: 55%
“…Most TRP channels are regulated by PIP 2 , a major phosphoinositide in the plasma membrane inner leaflet. Both positive and negative regulatory effects of PIP 2 have been reported in TRPV1 and other TRP channels, and there is evidence to suggest that multiple distinct binding sites account for these varied effects (Yazici et al, 2021). While phosphoinositides, such as PI antagonize TRPV1 activation by competing for vanilloid agonist binding, another site(s) likely mediates PIP 2 activation of TRPV1.…”
Section: Pip 2 and Other Lipid Binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interaction cannot be explained by direct contact between TM2 and TDh. Thus, it would not be unreasonable to suggest that this interaction between TM2 and the TDh involves an additional linker molecule such as PIP 2 or other lipid binding to this region (Poblete et al, 2014; Yin et al, 2017; Yazici et al, 2021; Hughes et al, 2018)). Interactions between the channel and the membrane at the cytosol-membrane interface is emerging as a common theme in TRPs.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, molecular docking and MD simulations have not been applied yet to study the binding of photoswitchable lipids to TRP channels. However, these two computational techniques have been extensively used to investigate channel modulation by other TRP ligands [ 58 , 59 , 60 , 61 , 62 ] and thus their use could be easily extended to photopharmacological applications.…”
Section: Computational Modeling Of Photoswitchable Ligands Targeting Voltage-gated Ion Channelsmentioning
confidence: 99%